Moving Patients Forward: Motivational Engagement - Clark, John Greer; Maatman, Carissa; Gailey, Lorraine (Seminars in Hearing, 2012)
Health care providers recognize that behavioral change does not occur without motivation for change. In hearing health, practitioners often employ external motivators as a means to engage patients within the treatment process. The strongest motivations for change, however, arise from within one's self. This article reviews motivational tools introduced to audiology through the Ida Institute as a means to help patients tap into their own internal motivation to more readily accept and act upon treatment recommendations.
Keywords: Motivation; behavioral change; engagement; self-assessment; counseling